Nuclear Import of Arabidopsis Poly(ADP-Ribose) Polymerase 2 Is Mediated by Importin-α and a Nuclear Localization Sequence Located Between the Predicted SAP Domains - Chen, Chao; Masi, Raffaella De; Lintermann, Ruth; Wirthmueller, Lennart (Frontiers in Plant Science, 2018)
Proteins of the poly(ADP-ribose) polymerase (PARP) family modify target proteins by covalent attachment of ADP-ribose moieties onto amino acid side chains. In Arabidopsis, PARP proteins contribute to repair of DNA lesions and modulate plant responses to various abiotic and biotic stressors. Arabidopsis PARP1 and PARP2 are nuclear proteins and given that their molecular weights exceed the diffusion limit of nuclear pore complexes, an active import mechanism into the nucleus is likely. Here we use confocal microscopy of fluorescent protein-tagged Arabidopsis PARP2 and PARP2 deletion constructs in combination with site-directed mutagenesis to identify a nuclear localization sequence in PARP2 that is required for nuclear import. We report that in co-immunoprecipitation assays PARP2 interacts with several isoforms of the importin-alpha group of nuclear transport adapters and that PARP2 binding to IMPORTIN-alpha2 is mediated by the identified nuclear localization sequence. Our results demonstrate that PARP2 is a cargo protein of the canonical importin-alpha/beta nuclear import pathway.